Legal and ethical essentials of health care administration - Pozgar, George D. (Burlington, MA : Jones & Barlett Learning, 2019)
"Legal and Ethical Essentials of Health Care Administration, Third Edition is more than an abridged version of Legal Aspects of Health Care Administration, Thirteenth Edition. The content has been updated and expanded to bring excitement into the learning process. This Second Edition delivers to the reader a comprehensive updated review of both health law and ethics. The substantive material in the Third Edition has been carefully selected based on the common legal and ethical issues the practitioner will face during his or her career. Although this book is mandatory reading for many students enrolled in health management and patient care courses, it is particularly valuable as a supplemental reading in the curricula of many healthcare programs"--
Keywords: Medical laws and legislation; Health services administration--Law and legislation; Medical personnel--Malpractice